Comparison of Mechanical Resistance to Maximal Torsion Stress in Original and Nonoriginal or Compatible Prosthetic Implant Screws: An In Vitro Study - António Sérgio Silva; José Manuel Mendes; Tiago Araújo; Carlos Aroso; Pedro Barreiros (International Journal of Dentistry)
Micromovements of the implant-abutment connection influence peri-implant bone preservation. The maximal torque after a cycle of implant prosthetic screw tightening using original components of different manufacturers and replicas produced by other companies is evaluated and quantified in this study. A total of 30 Mis Seven® standard platform implants and 30 interfaces were used, and 30 standard platform screws were tested, 10 Mis®, 10 Iconekt®, and 10 Exaktus®. The screws were tightened with an MIS® torquemeter until their respective fracture, and the fracture point was measured through the equipment’s load cell, CS-Dental Testing Machine®. The screws were analyzed under an Olympus® SZ61 microscope. The fracture points were recorded and compared among all samples. To compare the mean values of the fracture torques, t-tests were performed using the reference values associated with each brand and the sample results. The variable “Place of Fracture” between the original Mis® brand and the Exaktus® replica compared to the Iconekt® replica presented a statistically significant difference (p < 0.001). When analyzing the variable “Fracture Torque,” although it was verified that the replica screws (Iconekt® and Exaktus®) had a lower maximum torque, 65.11 Nm and 62.89 Nm, respectively, compared to the original Mis® brand (70 Nm and 69 Nm), there were no statistically significant differences p > 0.05. Nonoriginal screws did not present different fracture resistances compared to the original Mis® brand screws. The fracture site of Iconekt® screws showed a different pattern compared to the other brands.